Official development assistance and indigenous peoples (2011)
The past decade (1999-2010) saw an increase in Official Development Assistance (ODA) toward programs and projects that aim to reduce poverty in indigenous peoples' communities. Asset reform has been the centerpiece of ODA, along with the crafting of the Ancestral Domain Sustainable Development and Protection Plan (ADSDPP). A discourse analysis of documents pertinent to these programs and projects reveals that overall, ODA aims to integrate or mainstream indigenous peoples into the neo-liberal development framework. This situation has led to state, capital, and elite capture of the indigenous peoples movement's agenda of empowerment. As an illustrative example, the notion of individual and collective land rights has inevitably pushed indigenous peoples in a game where the more powerful players end up the winners. It is true that elements of indigenous peoples' agenda for development, such as customary law, indigenous knowledge, traditional livelihoods and schools of living tradition are now given more attention. However, these articulations of a "good life" by and for indigenous peoples are still tackled within modernist discourse, which domesticates alternative social imaginaries to growth-oriented development discourse.
Keywords: Official Development Assistance; Indigenous peoples -- Government relations; Indigenous peoples -- Legal status, laws, etc